LEGAL REGULATION OF STATE MANAGEMENT OF MEDICAL SCIENCE - L. S. Melnikova; O. Yu. Rebrova; V. V. Omelyanovskiy (Фармакоэкономика)
The article presents an analysis of the general legal regulation of medical research in Russian Federation. Issues to be improved are mentioned. The main legal act for management of scientific activities is the Federal Law of 23 August 1996 N 127-FZ "On Science and State Technical Policy". The basic legal norms of the law are outdated and need to be adjusted, and primar items to update are main concepts. Basic definitions of the law need to be clarified and brought into line with international law. In the allocation of budgetary resources and the planning of this activity it is essential to shift the attention from the control over the funds expenditure to the estimation of research results. This will facilitate more effective and transparent spending of budget funds for scientific research in Russian Federation.